Environmental assessment for predicting groundwater degradation of “Rey” municipality - Majid Ehteshami; Ali Sharifi (Numerical Methods in Civil Engineering)
Clean drinking water for the municipality of “Rey” with population of over one million remains a critical and serious problem. In particular, Rey’s continued water demands has caused a substantially high drop in its local groundwater level. With running this study, we can appropriately predict the quality of groundwater in Rey. In this study, we have considered presence of nitrate contaminant as the most suitable index representing groundwater contamination or pollution. For example, such index is capable of high solubility in water has a low absorption rate and exhibits relatively sustained compound stability. Moreover, the PMWIN software code was employed to model quality of associated aquifers. In addition, we analyzed data from Rey drinking water wells, which were collected and processed during the period of 2005 to 2012. We further evaluated: values of longitudinal and latitudinal diffusions, and absorption coefficient. A drop in the groundwater levels was measured 1.5 to 5 m for the eastern part of Rey and 5 to 11 m for the central zone of the municipality. For the western part of Rey, a drop in ground water levels in excess of 22 m were noted. In this paper, the value of Nitrate was determined and compared with standard values presented by EPA.